EDUKASI TEKNIK PENGAMBILAN DARAH KAPILER PADA PETUGAS LABORATORIUM RS MUHAMMADIYAH PALEMBANG - Bastian, Bastian; Hartati, Dewi (Khidmah, 2019)
Blood collection techniques are very important to do to help laboratory workers reduce the error rate at the preanalytic stage. Counseling on capillary blood collection techniques is carried out to laboratory workers at Muhammadiyah Palembang Hospital with educational methods through leaflets and perform capillary blood collection techniques which aim to improve the understanding of laboratory workers with total of 20 participants. In the results of counseling on capillary blood collection techniques, laboratory staff at Muhammadiyah Palembang Hospital already know that the techniques in capillary blood collection must be carried out properly so that the results are accurate, precise, and reliable for specimen collection. Specimen collection must be determined because it may be because taking a blood specimen is the beginning in determining a medical diagnosis.